Method for testing inter-permeation of dissimilar slurries
By measuring the interpenetration distance between the positive electrode slurry and other slurries in the coating device, the problem of difficulty in quickly detecting the interpenetration of slurry in the prior art is solved, and a rapid and accurate slurry interpenetration evaluation is achieved. Improves coating process efficiency and extreme sheet quality.
Patent Information
- Application Number
- CN202411716035.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-02-18
AI Technical Summary
The prior art is difficult to quickly detect the interpenetration between the positive electrode slurry containing different positive electrode dispersants and other slurries, resulting in low coating process efficiency and poor quality of the extreme sheet.
Using a test method for interpenetration of different types of slurry, the test is carried out by a coating device, which includes a coating element and a coating platform equipped with foils. The mutual interpenetration distance between the slurry is evaluated. seepage situation.
This method can quickly and accurately evaluate the impact of different positive electrode dispersants on the interpenetration between slurries, quickly screen out non-interpenetration samples, and improve the coating process efficiency and the quality of the electrode sheet.
Smart Images

Figure CN119470165A_ABST
Abstract
Description
Technical Field
[0001] The invention provides a testing method for interpenetration of heterogeneous slurries. Background Art
[0002] Lithium-ion batteries are widely used in electronic devices, electric vehicles and energy storage systems. Their performance and safety have strict requirements on the selection of battery materials and processing technology.
[0003] In lithium battery systems, the positive electrode will be cut into the designed size after coating. Burrs are very likely to appear on the edge of the electrode when cutting. Once the separator is pierced and the negative electrode is contacted, it will cause a short circuit in the battery. With the continuous upgrading and improvement of the lithium battery slurry coating process, boehmite has gradually entered the coating process system. Boehmite has a smooth surface and can fill the edge of the positive electrode after coating, making the surface smooth and burr-free after cutting. At the same time, it has high temperature resistance, electrical insulation and excellent chemical stability, which makes it widely used in the positive electrode coating process.
[0004] During the coating process of the lithium-ion battery production line, the positive electrode slurry will be affected by the positive electrode dispersant, resulting in changes in the surface tension, viscosity and fluidity of the slurry, which will cause the two slurries to interpenetrate to varying degrees, that is, the two slurries penetrate each other or a single slurry penetrates into another slurry, which greatly affects the coating progress and the quality of the pole piece. In the patent application CN116564615A, a coating pole piece preparation mode of boehmite slurry and electrode slurry is introduced, but there is a lack of evaluation methods for slurry interpenetration, and the coating process using a lithium battery coating machine is relatively cumbersome, with large resource investment and a long evaluation cycle, resulting in a slow evaluation speed. It can be seen that the existing technology detection requires the use of a large coating machine with two slurries for simultaneous coating. This method is relatively cumbersome and complex, with low efficiency and high loss.
[0005] Therefore, "how to quickly detect the interpenetration between positive electrode slurry containing different positive electrode dispersants and other slurries, so as to quickly determine the influence of positive electrode dispersants (or "positive electrode additives") on the interpenetration between positive electrode slurry and other slurries" has become an urgent problem to be solved. Summary of the invention
[0006] In order to overcome the defect of the prior art that "it is difficult to quickly detect the interpenetration between positive electrode slurry containing different positive electrode dispersants and other slurries", the present invention provides a test method for the interpenetration of heterogeneous slurries. The method aims to quickly and accurately evaluate the influence of different positive electrode dispersants on the interpenetration between slurries, so as to quickly screen out non-interpenetrating samples, help distinguish sample differences, and improve coating process efficiency and pole piece quality; preferably, the method can be used for the rapid test of interpenetration of lithium-ion battery positive electrode slurry and boehmite slurry coating.
[0007] The present invention solves the above technical problems through the following technical solutions:
[0008] The present invention provides a method for testing the interpenetration of heterogeneous slurries, which is carried out by using a coating device, wherein the coating device comprises a coating element and a coating platform provided with a foil, wherein the coating element is arranged above the coating platform; the coating element comprises a base, and a stop bar and at least one stop plate arranged on the base, wherein the stop plate is vertically arranged on at least one side of the stop bar and connected to the stop bar;
[0009] The testing method for interpenetration of heterogeneous slurries comprises the following steps:
[0010] S1, placing the first slurry and the second slurry on the same side of the bar and on different positions of the foil on both sides of the baffle;
[0011] S2, using the coating element to perform coating to obtain a foil coated with a wet film, wherein the wet film is formed by contact between the first slurry and the second slurry; the coating speed is 15-25 mm / s, and the thickness of the wet film is 150-250 μm;
[0012] S3, drying the foil coated with the wet film, and measuring the interpenetration distance between the first slurry and the second slurry.
[0013] In the present invention, "interpenetration distance" refers to the farthest distance from the coating separation line (baffle) of the two slurries to one slurry in the area of the other slurry; by measuring the interpenetration distance between the first slurry and the second slurry, the interpenetration of the heterogeneous slurries can be determined; that is, when the area of the first slurry has the second slurry, or the area of the second slurry has the first slurry, and the interpenetration distance is not 0, there is interpenetration between the two slurries; when the first slurry and the second slurry are both in their respective areas and the interpenetration distance is 0, it means that there is no interpenetration between the two slurries.
[0014] In the present invention, those skilled in the art should know that in order to use the method of the present application to examine the interpenetration of heterogeneous slurries, the colors of the two slurries need to be clearly different.
[0015] In some embodiments, in step S2, the coating speed is 18-22 mm / s, for example, 20 mm / s.
[0016] In some embodiments, the wet film has a thickness of 180-220 μm, such as 200 μm.
[0017] In some embodiments, along the cross-sectional direction of the coating element, the angle between the surface of the base and the coating platform is 45°-75°, for example, 45°.
[0018] In some embodiments, the number of the baffles is at least 2, and each of the baffles is vertically disposed on the same side of the baffle bar; by providing a plurality of baffles, a variety of samples can be coated simultaneously.
[0019] In some embodiments, the baffle bar is arranged on the base along the central axis of the base, the number of the baffle plates is 4, and every two baffle plates are symmetrically arranged on both sides of the baffle bar to form a middle material trough and two side material troughs arranged on both sides of the middle material trough.
[0020] In a specific embodiment, the length of the coating element is 200 mm; wherein the length of the coating element refers to the dimension of the coating element perpendicular to the coating direction.
[0021] In a specific embodiment, the width of the coating element is 24.38 mm; wherein the width of the coating element refers to the size of the coating element in the coating direction.
[0022] In a specific embodiment, the height of the coating element is 15.57 mm.
[0023] In a specific embodiment, the length of the intermediate trough is 90 mm.
[0024] In a specific embodiment, the length of each side material groove is 30 mm.
[0025] In a specific implementation, the thickness of the stop bar is 0.5 mm.
[0026] In some embodiments, the foil comprises aluminum foil; preferably, the length of the foil is 300-350 mm; preferably, the width of the foil is 200-250 mm.
[0027] In the present invention, the wet film coated on the foil needs to meet certain dimensional requirements.
[0028] In the present invention, the coated wet film length refers to the size of the wet film in the coating direction.
[0029] In some embodiments, the coated wet film length is 300-350 mm; those skilled in the art should know that the coated length should be smaller than the length of the foil.
[0030] In the present invention, the coated wet film width refers to the size of the wet film perpendicular to the coating direction.
[0031] In some embodiments, the width of the coated wet film is 120 mm; the coating size width refers to the width of the wet film, that is, the sum of the widths of the first slurry and the second slurry.
[0032] In some embodiments, the drying process is performed in an oven.
[0033] In some embodiments, the drying process is carried out at a temperature of 110-130°C.
[0034] In some embodiments, the drying process lasts for 20-30 minutes.
[0035] In some embodiments, the measuring tool is a vernier caliper; preferably, the accuracy of the vernier caliper is 0.001 mm.
[0036] In some embodiments, the measured area is an area 10-20 cm away from the coating starting point along the coating direction.
[0037] In some embodiments, the first slurry includes a positive electrode slurry; preferably, the solid content of the positive electrode slurry is 45% to 65%, % is the percentage of the solid mass in the positive electrode slurry to the total mass of the positive electrode slurry; preferably, the viscosity of the positive electrode slurry is 5000-80000cp. "cp" is centipoise, 1 Pa·s = 1000 cp.
[0038] In a specific embodiment, the positive electrode slurry includes a positive electrode active material, a first binder, a first conductive agent, a positive electrode dispersant and a first solvent, and the mass ratio of the positive electrode active material, the first binder and the first conductive agent is (95~98): (0.5~2.5): (1~2.5); the mass of the positive electrode dispersant accounts for 0.1%~0.3% of the total mass of the positive electrode slurry; preferably, the positive electrode active material is one or more of lithium iron phosphate (LFP), lithium cobalt oxide (LCO), nickel cobalt manganese ternary material (NCM), and lithium manganese iron phosphate (LMFP); preferably, the first binder is polyvinylidene fluoride (PVDF); preferably, the first conductive agent is one or more of conductive carbon black, conductive graphite, Ketjen black, and acetylene black; preferably, the first solvent includes N-methylpyrrolidone (NMP).
[0039] Wherein, the weight of the positive electrode slurry can be 150~300g.
[0040] In a preferred embodiment, the method for preparing the positive electrode slurry comprises the following steps:
[0041] s1. stirring and mixing the first binder and the first solvent to obtain a first adhesive solution with a solid content of 5% to 10%;
[0042] s2, stirring the first glue solution and the positive electrode dispersant to obtain a first mixed solution;
[0043] s3, stirring and mixing the first mixed solution, the positive electrode active material, and the first conductive agent, and then sequentially performing degassing, cooling, and screening treatments.
[0044] Wherein, the equipment used in the method for preparing the positive electrode slurry may be a homogenizing and degassing machine.
[0045] Preferably, in step s1, the revolution speed of the stirring and mixing is 1000-1500 rpm, the rotation speed of the stirring and mixing is 1000-1500 rpm, and the time of the stirring and mixing is 60-80 min.
[0046] In the present invention, the revolution refers to the rotation of the stirring container of the homogenizer and deaerator around the center point, and the rotation refers to the rotation of the stirring tank inside the homogenizer and deaerator on its own axis.
[0047] Preferably, in step s2, the revolution speed of stirring is 1000-1500 rpm, the rotation speed of stirring is 1000-1500 rpm, and the stirring time is 10 min.
[0048] Among them, preferably, in step s3, the stirring and mixing includes a first stirring and mixing and a second stirring and mixing in sequence, the rotation speed of the first stirring and mixing is 300~500rpm, the revolution of the first stirring and mixing is 300~500rpm, and the time of the first stirring and mixing is 30min; the revolution speed of the second stirring and mixing is 1000~1500rpm, the rotation speed of the second stirring and mixing is 1000~1500rpm, and the time of the second stirring and mixing is 40~60min.
[0049] Preferably, in step s3, the degassing time is 1 to 5 minutes.
[0050] Preferably, in step s3, the end point temperature of the cooling is room temperature, which is the room temperature commonly understood in the art, i.e., 25°C.
[0051] Preferably, in step s3, the screen size of the screening process is 150 mesh.
[0052] In some embodiments, the second slurry includes boehmite slurry; preferably, the solid content of the boehmite slurry is 20%~45%, % is the percentage of the solid mass in the boehmite slurry to the total mass of the boehmite slurry; preferably, the viscosity of the positive electrode slurry is 5000-80000cp.
[0053] In a specific embodiment, the boehmite slurry includes a boehmite material, a second binder and a second solvent, and the mass ratio of the boehmite material to the second binder is (75~85):(20~25); preferably, the boehmite material includes boehmite; preferably, the second binder includes polyvinylidene fluoride (PVDF) or polyvinylidene fluoride (HSV); preferably, the second solvent includes N-methylpyrrolidone (NMP).
[0054] Preferably, the total weight of the boehmite slurry is 150-250 g.
[0055] Wherein, the polyvinylidene fluoride may be PVDF5130.
[0056] Wherein, the polyvinylidene fluoride may be HSV900.
[0057] In a preferred embodiment, the method for preparing the boehmite slurry comprises the following steps:
[0058] ss1. Stirring and mixing the second binder and the second solvent to obtain a second adhesive solution with a solid content of 5% to 25%;
[0059] ss2. Stir the second glue and the boehmite material; then cool down and screen them in sequence.
[0060] Preferably, in step ss1, the stirring and mixing speed is 500-1000 rpm, and the stirring and mixing time is 5-15 min.
[0061] Preferably, in step ss2, the stirring speed is 2000-2500 rpm, and the stirring time is 150-180 min.
[0062] Preferably, in step ss2, the end point temperature of the cooling is room temperature, which is the room temperature commonly understood in the art, i.e., 25°C.
[0063] Preferably, in step ss2, the screen size of the screening process is 150 mesh.
[0064] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.
[0065] The reagents and raw materials used in the present invention are commercially available.
[0066] The positive and progressive effects of the present invention are:
[0067] (1) The method of the present invention aims to quickly and accurately evaluate the effects of different cathode dispersants on the interpenetration between slurries, thereby quickly screening out non-interpenetrating samples, helping to distinguish sample differences, and improving coating process efficiency and electrode quality; preferably, the method can be used for rapid testing of interpenetration between lithium-ion battery cathode slurry and boehmite slurry coating.
[0068] (2) The method of the present invention can quickly screen interpenetration samples, and the slurry homogenization and coating occupy and consume very few resources, thereby reducing the investment in materials and equipment, reducing the evaluation cost, and simplifying the overall test process. BRIEF DESCRIPTION OF THE DRAWINGS
[0069] Figure 1 This is a three-dimensional structural diagram of the coating element in Example 1 of the present application;
[0070] Figure 2 is a cross-sectional view of the coating element at the baffle in Example 1 of the present application;
[0071] Figure 3 This is a photo of the interpenetration effect between the positive electrode slurry and the boehmite slurry in Example 1 of the present application;
[0072] Figure 4 This is a photo of the interpenetration effect between the positive electrode slurry and the boehmite slurry in Example 2 of the present application;
[0073] Figure 5 This is a photo of the interpenetration effect between the positive electrode slurry and the boehmite slurry in Example 3 of the present application;
[0074] Figure 6 This is a photograph of the interpenetration effect of the positive electrode slurry and the boehmite slurry in Example 4 of the present application.
[0075] Description of reference numerals:
[0076] Coating element 1
[0077] Pedestal 101
[0078] Bar 102
[0079] Baffle 103
[0080] Intermediate trough 104
[0081] Side material trough 105. DETAILED DESCRIPTION
[0082] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.
[0083] Examples 1-4 studied the interpenetration between the positive electrode slurry and the boehmite slurry, wherein the raw material compositions and preparation methods of the positive electrode slurry and the boehmite slurry used are as follows:
[0084] The positive electrode slurry is composed of the following substances: lithium iron phosphate as the positive electrode active material, polyvinylidene fluoride (HSV900) as the first binder, conductive carbon black (SP) as the first conductive agent, positive electrode dispersant, and N-methyl-2-pyrrolidone (NMP) as the first solvent. Among them, the mass percentage of the positive electrode active material, binder, conductive agent and positive electrode dispersant is 97.2:1.8:0.7:0.3. The total mass of the positive electrode slurry is 280g, and the solid content of the positive electrode slurry is 45~65%.
[0085] Using the above raw material composition, the homogenization steps of the positive electrode slurry in the homogenization degassing machine are as follows:
[0086] (1) The first binder HSV900 and the first solvent NMP were mixed into a glue solution at a solid content of 6%, and positive electrode dispersant 1# or positive electrode dispersant 2# was added, and stirred for 10 minutes, wherein positive electrode dispersant 1# was a phosphate positive electrode dispersant and positive electrode dispersant 2# was an acrylate positive electrode dispersant;
[0087] (2) Add lithium iron phosphate and conductive carbon black SP, set the revolution speed to 400 rpm, the rotation speed to 308 rpm, and the stirring time to 30 minutes. Then change the revolution speed to 1340 rpm, the rotation speed to 1340 rpm, and the stirring time to 40 minutes. Revolution refers to the rotation of the mixing container of the homogenizer deaerator around the center point, and rotation refers to the rotation of the mixing tank inside the homogenizer deaerator on its own axis.
[0088] (3) After stirring, set the revolution to 1400 rpm and degas for 90 seconds. After taking out, lower the room temperature to 25°C, sieve the material with a 150-mesh sieve, and test the viscosity.
[0089] The boehmite slurry is composed of the following substances: alumina BG-613 as the boehmite material, HSV900 as the second binder, and NMP as the second solvent, wherein the mass percentage of boehmite and the binder is 80:20, the total mass of the boehmite slurry is 200g, and the solid content of the boehmite slurry is 20%~45%.
[0090] Using the above raw material composition, the homogenization steps of the boehmite slurry in the homogenizer and deaerator are as follows:
[0091] (1) The second binder HSV900 and the second solvent NMP were mixed into a glue solution at a solid content of 8%, NMP was added, and the mixture was stirred at 1000 rpm for 5 min. Boehmite was added and the mixture was stirred at 2500 rpm for 150 min.
[0092] (2) After stirring, cool the temperature to 25°C, sieve the material using a 200-mesh sieve, and test the viscosity.
[0093] Example 1
[0094] This embodiment is a test method for the interpenetration of heterogeneous slurries, which is carried out using a coating device.
[0095] Figure 1 is a three-dimensional structural diagram of the coating element in this embodiment; Figure 2 It is a front view of the coating element in this embodiment.
[0096] The coating device includes a coating element 1 and a coating platform provided with a foil, wherein the coating element 1 is arranged above the coating platform; the coating element 1 includes a base 101, a stop bar 102 and four baffles 103 arranged on the central axis of the base 101, and each two baffles 103 are symmetrically arranged on both sides of the stop bar 102 to form an intermediate material trough 104 and two side material troughs 105 arranged on both sides of the intermediate material trough 104; along the cross-sectional direction of the coating element 1, the angle between the surface of the base 101 and the coating platform is 45°. The length, width and height of the coating element 1 are 200 mm, 24.38 mm and 15.57 mm respectively; the length of the intermediate material trough 104 is 90 mm; the length of each side material trough 105 is 30 mm; the thickness of the stop bar 102 is 0.5 mm. The foil includes aluminum foil; the length and width of the foil are 350 mm and 200 mm respectively.
[0097] The test method for interpenetration of dissimilar slurries includes the following steps:
[0098] S1, placing the first slurry and the second slurry on the same side of the bar 102 and on different positions on the foils on both sides of the baffle 103; wherein the first slurry is a positive electrode slurry with a solid content of 62% and a viscosity of 19300 cp, and the positive electrode dispersant in the positive electrode slurry is positive electrode dispersant 1#, and the second slurry is a boehmite slurry with a solid content of 25% and a viscosity of 5500 cp;
[0099] S2, coating with coating element 1 to obtain a foil coated with a wet film, wherein the wet film is formed by contact between the first slurry and the second slurry; the coating speed is 20 mm / s, and the thickness of the wet film is 200 μm; the length and width of the coated wet film are 300 mm and 120 mm, respectively;
[0100] S3. Dry the foil coated with the wet film and measure the interpenetration distance between the first slurry and the second slurry; wherein the temperature of the blast oven used for the drying process is 120° C., the drying time is 30 minutes, and a micrometer is used to measure and record the interpenetration conditions and interpenetration gap of the two materials.
[0101] Example 2
[0102] This embodiment is a test method for interpenetration of heterogeneous slurries. In step S1 of the test method, the first slurry is a positive electrode slurry with a solid content of 62% and a viscosity of 9520 cp, the positive electrode dispersant in the positive electrode slurry is positive electrode dispersant 2#, and the second slurry is a boehmite slurry with a solid content of 25% and a viscosity of 5500 cp;
[0103] The coating device and other steps and conditions used in this test method are the same as those in Example 1.
[0104] Example 3
[0105] This embodiment is a test method for interpenetration of heterogeneous slurries. In step S1 of the test method, the first slurry is a positive electrode slurry with a solid content of 67% and a viscosity of 36960 cp, the positive electrode dispersant in the positive electrode slurry is positive electrode dispersant 1#, and the second slurry is a boehmite slurry with a solid content of 25% and a viscosity of 5500 cp;
[0106] The coating device and other steps and conditions used in this test method are the same as those in Example 1.
[0107] Example 4
[0108] This embodiment is a test method for interpenetration of heterogeneous slurries. In step S1 of the test method, the first slurry is a positive electrode slurry with a solid content of 67% and a viscosity of 11250 cp, the positive electrode dispersant in the positive electrode slurry is positive electrode dispersant 2#, and the second slurry is a boehmite slurry with a solid content of 25% and a viscosity of 5500 cp;
[0109] The coating device and other steps and conditions used in this test method are the same as those in Example 1.
[0110] Effect Example 1
[0111] This effect example tests the interpenetration of the two slurries of Examples 1-4. Figure 3 This is a photo of the interpenetration effect between the positive electrode slurry and the boehmite slurry in Example 1; Figure 4 This is a photo of the interpenetration effect between the positive electrode slurry and the boehmite slurry in Example 2; Figure 5 This is a photo of the interpenetration effect between the positive electrode slurry and the boehmite slurry in Example 3; Figure 6 This is a photograph of the interpenetration effect of the positive electrode slurry and the boehmite slurry in Example 4.
[0112] Depend on Figure 3 and Figure 5 It can be seen that the cathode slurry and boehmite slurry are both in their respective regions, and the interpenetration distance is 0. There is no interpenetration between the two slurries; however, Figure 4 and Figure 6 In the process, the black positive electrode slurry partially penetrates into the white boehmite slurry area, which is called "black eating white"; the interpenetration distance is the farthest distance from the coating separation line (baffle) between the positive electrode slurry and boehmite to the positive electrode slurry in the boehmite area.
[0113] Table 1 is thus obtained, which shows the differences between the test objects of Examples 1-4 and the analysis of the interpenetration.
[0114] Table 1
[0115]
[0116] As shown in Table 1, after adding positive electrode dispersant 1# to the positive electrode slurry, the positive electrode slurry and the boehmite slurry do not interpenetrate, but after adding positive electrode dispersant 2# to the positive electrode slurry, the positive electrode slurry and the boehmite slurry interpenetrate. It can be seen that the method of the present application can quickly and accurately evaluate the influence of different positive electrode dispersants on the interpenetration between slurries, thereby quickly screening out non-interpenetrating samples, helping to distinguish sample differences, and improving coating process efficiency and pole piece quality; this method can be used for rapid testing of interpenetration of positive electrode slurry and boehmite slurry coating of lithium-ion batteries.
Claims
1. A test method for interpenetration of heterogeneous slurries, characterized in that: The coating is carried out by using a coating device, the coating device comprises a coating element and a coating platform provided with a foil, the coating element is arranged above the coating platform; the coating element comprises a base, a stop bar and at least one baffle arranged on the base, the baffle is vertically arranged on at least one side of the stop bar and connected to the stop bar; The testing method for interpenetration of heterogeneous slurries comprises the following steps: S1, placing the first slurry and the second slurry on the same side of the bar and on different positions of the foil on both sides of the baffle; S2, using the coating element to perform coating to obtain a foil coated with a wet film, wherein the wet film is formed by contact between the first slurry and the second slurry; the coating speed is 15-25 mm / s, and the thickness of the wet film is 150-250 μm; S3, drying the foil coated with the wet film, and measuring the interpenetration distance between the first slurry and the second slurry.
2. The method for testing interpenetration of heterogeneous slurries according to claim 1, characterized in that: In step S2, the coating speed is 18-22 mm / s, for example, 20 mm / s; And / or, the thickness of the wet film is 180-220 μm, for example, 200 μm.
3. The method for testing interpenetration of heterogeneous slurries according to claim 1, characterized in that: The coating element satisfies one or more of the following conditions ①-③: ① Along the cross-sectional direction of the coating element, the angle between the surface of the base and the coating platform is 45°-75°, for example, 45°; ② The number of the baffles is at least 2, and each baffle is vertically arranged on the same side of the baffle bar; ③ The baffle bar is arranged on the base along the central axis of the base, the number of the baffle plates is 4, and every two baffle plates are symmetrically arranged on both sides of the baffle bar to form a middle material trough and two side material troughs arranged on both sides of the middle material trough.
4. The method for testing interpenetration of heterogeneous slurries according to claim 3, characterized in that: The coating element satisfies one or more of the following conditions: ① The length of the coating element is 200 mm; ② The width of the coating element is 24.38 mm; ③ The height of the coating element is 15.57 mm; ④The length of the intermediate trough is 90 mm; ⑤ The length of each side trough is 30 mm; ⑥The thickness of the strip is 0.5 mm.
5. The method for testing interpenetration of heterogeneous slurries according to claim 1, characterized in that: The foil comprises aluminum foil; preferably, the length of the foil is 300-350 mm; preferably, the width of the foil is 200-250 mm; And / or, the coated wet film length is 300-350 mm; And / or, the coated wet film width is 120 mm.
6. The method for testing interpenetration of heterogeneous slurries according to claim 1, characterized in that: The drying process satisfies one or more of the following conditions: ① The drying process is carried out in an oven; ② The drying temperature is 110-130°C; ③ The drying time is 20-30 min; And / or, the measuring tool is a vernier caliper; preferably, the accuracy of the vernier caliper is 0.001 mm; And / or, the measured area is an area 10-20 cm away from the coating starting point along the coating direction.
7. The method for testing interpenetration of heterogeneous slurries according to claim 1, characterized in that: The first slurry includes a positive electrode slurry; preferably, the solid content of the positive electrode slurry is 45%-65%, % is the percentage of the solid mass in the positive electrode slurry to the total mass of the positive electrode slurry; preferably, the viscosity of the positive electrode slurry is 5000-80000cp; And / or, the second slurry includes boehmite slurry; preferably, the solid content of the boehmite slurry is 20%~45%, % is the percentage of the solid mass in the boehmite slurry to the total mass of the boehmite slurry; preferably, the viscosity of the positive electrode slurry is 5000-80000cp.
8. The method for testing interpenetration of heterogeneous slurries according to claim 7, characterized in that: The positive electrode slurry comprises a positive electrode active material, a first binder, a first conductive agent, a positive electrode dispersant and a first solvent, wherein the mass ratio of the positive electrode active material, the first binder and the first conductive agent is (95-98): (0.5-2.5): (1-2.5); the mass of the positive electrode dispersant accounts for 0.1%-0.3% of the total mass of the positive electrode slurry; preferably, the positive electrode active material is one or more of lithium iron phosphate, lithium cobalt oxide, nickel cobalt manganese ternary material and lithium manganese iron phosphate; preferably, the first binder is polyvinylidene fluoride; preferably, the first conductive agent is one or more of conductive carbon black, conductive graphite, Ketjen black and acetylene black; preferably, the first solvent comprises N-methylpyrrolidone; And / or, the boehmite slurry comprises a boehmite material, a second binder and a second solvent, and the mass ratio of the boehmite material to the second binder is (75~85):(20~25); preferably, the boehmite material comprises boehmite; preferably, the second binder comprises polyvinylidene fluoride or polyvinylidene fluoride; preferably, the second solvent comprises N-methylpyrrolidone.
9. The method for testing interpenetration of heterogeneous slurries according to claim 8, characterized in that: The method for preparing the positive electrode slurry comprises the following steps: s1. stirring and mixing the first binder and the first solvent to obtain a first adhesive solution with a solid content of 5% to 10%; s2, stirring the first glue solution and the positive electrode dispersant to obtain a first mixed solution; s3, stirring and mixing the first mixed solution, the positive electrode active material, and the first conductive agent, and then sequentially performing degassing, cooling, and screening treatments.
10. The method for testing interpenetration of heterogeneous slurries according to claim 8, characterized in that: The preparation method of the boehmite slurry comprises the following steps: ss1. Stirring and mixing the second binder and the second solvent to obtain a second adhesive solution with a solid content of 5% to 25%; ss2. Stir the second glue and the boehmite material; then cool down and screen them in sequence.
Citation Information
Patent Citations
Pole piece processing method, pole piece processing equipment and pole piece
CN116564615A